Sustainable Journeys: Rethinking Travel for the Future - Sobirov Bobur Baxtishodovich (Lembaga Bale Literasi, 2025)
This study explores the evolving discourse on sustainable travel amid increasing ecological crises and climate change. As traditional travel and tourism practices continue to contribute significantly to greenhouse gas emissions, biodiversity loss, and socio-economic disparities, this research aims to examine alternative travel paradigms that align with sustainability principles. Using a qualitative, literature-based methodology, the study synthesizes findings from interdisciplinary sources, including environmental science, tourism studies, policy reports, and technological innovations. The research identifies major themes such as the environmental footprint of tourism, the socio-cultural responsibilities of travelers, and the role of digital platforms in shaping travel behavior. Key findings reveal persistent challenges such as the prioritization of profit over ecological and social wellbeing, the marginalization of rural and indigenous perspectives, and the disconnect between travelers’ intentions and behaviors. Additionally, the study uncovers opportunities in community-based tourism, carbon reduction strategies, and ethical governance models. The paper calls for a comprehensive paradigm shift toward a regenerative travel ethic that promotes environmental integrity, intercultural respect, and equitable economic development. By filling theoretical and practical gaps, particularly in localized and behavioral dimensions, the study contributes to a more holistic understanding of sustainable travel. It ultimately advocates for collaborative, multi-stakeholder approaches that redefine travel as a vehicle for global stewardship and long-term ecological resilience.